STRATEGI KEPEMIMPINAN DALAM MENGELOLA KEAMANAN ARSIP PENDIDIKAN - Habna Pranita; Rafli Ahmad Mualin; Sifa Nurmaulidia; Silmi Millatul’ulyaa; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the importance of educational record security as a strategic asset and collective memory of institutions, which currently face risks of physical damage and cyberattacks in the digital era. The purpose of this study is to analyze the most effective leadership strategies in ensuring the security of educational records. The method used is library research with a qualitative approach, where data is analyzed through coding, categorization, and interpretation techniques. The results indicate that leadership implementing visionary navigation, strengthening social capital, and based on ecotheological values can create a robust risk mitigation system. Furthermore, leadership characteristics that emphasize detail and precision are proven effective in fostering a quality culture in record management. The synergy between leadership, information technology, and organizational policy is the primary key to maintaining data sovereignty and the integrity of educational information. Keywords: Leadership Strategy, Record Security, Education, Visionary Navigation, Social Capital